2022
DOI: 10.3390/pharmaceutics14010181
|View full text |Cite
|
Sign up to set email alerts
|

Receptor Specificity Engineering of TNF Superfamily Ligands

Abstract: The tumor necrosis factor (TNF) ligand family has nine ligands that show promiscuity in binding multiple receptors. As different receptors transduce into diverse pathways, the study on the functional role of natural ligands is very complex. In this review, we discuss the TNF ligands engineering for receptor specificity and summarize the performance of the ligand variants in vivo and in vitro. Those variants have an increased binding affinity to specific receptors to enhance the cell signal conduction and have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 151 publications
0
5
0
Order By: Relevance
“…The two primary mechanisms necessary for the induction of apoptosis are the intrinsic pathway and the extrinsic pathway mediated by the death receptor (regulated at the level of mitochondria). The Fas-associated death domain (FADD) is recruited through molecule signals (Fas / FasL) on the surface in the extrinsic pathway 48 . The procaspase-8 gene can be activated by the FADD-Fas complex.…”
Section: Resultsmentioning
confidence: 99%
“…The two primary mechanisms necessary for the induction of apoptosis are the intrinsic pathway and the extrinsic pathway mediated by the death receptor (regulated at the level of mitochondria). The Fas-associated death domain (FADD) is recruited through molecule signals (Fas / FasL) on the surface in the extrinsic pathway 48 . The procaspase-8 gene can be activated by the FADD-Fas complex.…”
Section: Resultsmentioning
confidence: 99%
“…The overall RSD value of 2.4% obtained for the current signals measured for the individual mixing of other cytokines with TNF-α and all together, with a maximum relative signal variation of 5%, confirmed that the selective detection of TNF-α cytokine could be achieved in the multicytokine sample matrix (Figure Biv). These findings were in agreement with early reports on cytokine–receptor interactions. , …”
Section: Resultsmentioning
confidence: 99%
“…These findings were in agreement with early reports on cytokine−receptor interactions. 33,34 The use of the specific detection antibody and standard HRP-TMB system enhanced the sensitivity of the biomembrane sensor. The analytical performance of the cell membrane-based bioelectronic chip for the sensitive detection of various TNF-α concentrations in the presence of IL-6 cytokine was also studied.…”
Section: Analytical Performance Of the Hybrid Cellmentioning
confidence: 99%
“…As of today, the extrinsic and intrinsic pathways are the two main apoptosis pathways, and the perforin/granzyme pathway as a T-cell mediated signal route has also been defined. The extrinsic pathway is initiated through interactions of ligands with transmembrane receptors of the tumor necrosis factor (TNF) superfamily, such as TNF-α/TNFR1, FasL/Fas, TRAIL/DR4 or DR5, VEGI/DR3 and TWEAK/Fn14 [31][32][33][34][35][36][37]. The ligand binds to the receptor to recruit adaptor proteins (FADD, TRADD) to activate the caspase cascade and trigger apoptosis [38][39][40].…”
Section: Apoptosismentioning
confidence: 99%